Decolonizing Spaces from Disability: A fight from social networks to achieve inclusive cities - Parra Gómez, Sheila (Street Art & Urban Creativity, 2025)
The transformation of cities into accessible and inclusive places for people with disabilities, despite decades of work, remains a pending subject in most aspects. Escaping from mere quantitative data, this work, which is part of a thesis, focuses on the sociopolitical dimension of disability culture in a post-qualitative key, to find the needs and concerns that move the group in the agenda for an inclusive city. To achieve this goal, a digital and visual ethnographic methodology was followed on the social networks Instagram and X, through a digital diary, 21 semi-structured interviews and a corpus of 100 images. The results point to the proliferation of inclusive parks, beaches, races and changing rooms, to the denunciation of unjust situations and the exhibition of other normalized ones, to achieve decolonizing the spaces and making the well-being of the collective the norm.